Structure and bonding of IrB12−: converting a rigid boron B12 platelet to a Wankel motor. Issue 32 (14th March 2016) - Liu, Lei; Moreno, Diego; Osorio, Edison; Castro, Abril C.; Pan, Sudip; Chattaraj, Pratim K.; Heine, Thomas; Merino, Gabriel
Abstract : B12 is a rigid cluster with a high inner ring rotational energy barrier. However, doping it with Ir lowers the barrier significantly, transforming the IrB12 − cluster in a Wankel motor. Abstract : The global minimum of IrB12 − is a C 3v symmetric bowl-like structure in which the Ir atom is located on the concave side of the bowl, similar to its lighter congeners, CoB12 − and RhB12 − clusters. Although all these MB12 − (M = Co, Rh, Ir) clusters show dynamical behaviour, analogous to that of the so-called 'Wankel motors', the energy barrier for the rotation of the inner B3 ring within the peripheral B9 ring is the lowest in the IrB12 − case (5.0 kcal mol −1 only). The geometrical feature along with the lower interaction energy between B3 and MB9 moieties are responsible for a smaller rotational energy barrier in IrB12 − than those in CoB12 − and RhB12 − clusters.